Screening and Diagnosis of Gestational Diabetes- A Review Study - Mozhgan Karimifar; Mansour Siavash (مجله دانشکده پزشکی اصفهان)
Gestational diabetes (GDM) refers to diagnosis of diabetes at 24 to 28 weeks of pregnancy. GDM fetuses and mothers are at risk for numerous adverse outcomes. Diabetes screening should be done before pregnancy in all high-risk women who plan to become pregnant. GDM screening at 24 to 28 weeks of pregnancy with one-stage or two-stage method is recommended in all women. The criteria for diagnose of diabetes in the first perinatal visit and before the 15th week of pregnancy to detect undiagnosed diabetes are the same as the standard criteria for diagnosing diabetes in non-pregnant people. Women who have a glucose metabolism disorder before the 15th week of pregnancy are at a higher risk for maternal and infant complications. In addition, with the progress of pregnancy, they may need insulin and the risk of GDM is higher in them. Fasting glucose of 110-125 mg/dl and HbA1C of about 5.9-6.4% before the 15th week of pregnancy is known as glucose metabolism disorder, blood glucose monitoring is recommended in these women. Women with GDM should have a glucose tolerance test 4 to 12 weeks after delivery. The criteria for diagnose of diabetes at this time are the same as for non-pregnant people. All women with GDM should be screened for diabetes and prediabetes every 3 years.